SYSTEM PROTECTION PATENT THE RESULTS OF INVENTIONS IN THE FIELD OF TECHNOLOGY - Zulfikri Zulfikri (Universitas Riau, 2021)
Patent is the exclusive right of the inventor to the invention in the field of technology for a certain period of time to carry out himself or give approval to other parties to carry out his invention. It is necessary to provide legal protection for every intellectual work in the form of this patent related to technology, so that the ownership rights of the patent holder are guaranteed. On the other hand, patent protection can provide incentives for inventors to make new innovations through exclusive rights to the inventions they produce. The legal system in Indonesia states that the protection of patents will follow the type of patent. Ordinary Patents will be protected for 20 years from the receipt of the patent application, while Simple Patents will be protected for 10 years from the receipt of the patent application. For companies or industries with patents, companies have strong evidence that all ideas and products produced are original from the company without duplicating products from other parties. This will increase consumer confidence and dedication to the company. Copyrights that protect all forms of ideas and works of the company are also an important asset for the recognition of the company's inventions. Patents are also very legal and become an important asset in the confirmation of inventions.